The Price Equilibrium Existence Problem in Topological Vector Lattices - Mas-Colell, Andreu (Econometrica, 1986)
[A price equilibrium existence theorem is proved for exchange economies whose consumption sets are the positive orthant of arbitrary topological vector lattices. The motivation comes from economic applications showing the need to bring within the scope of equilibrium theory commodity spaces whose positive orthant has empty interior, a typical situation in infinite dimensional linear spaces.]